Archival insights into vulnerability and risk management during the early Spanish colonial period (1598–1680 AD) in New Mexico. (December 2022) - Dawson, Emily; Trigg, Heather
Risk and vulnerability are especially acute for colonizing populations due to their limited knowledge of the environment in newly settled areas and constrained social networks. Focusing on the initial settlement of the New Mexico colony, this paper examines the social response of Spanish colonists to vulnerability and risk during the early colonial period (AD 1598–1680). We use historical documents and modern weather records to assess the strategies implemented by 17th-century colonists to mitigate their vulnerability to the effects of unfamiliar, arid environmental conditions. The Spanish Crown had developed risk-reducing practices that encouraged successful establishment of colonies, including technological methods such as irrigation ditches and social methods such as tithing. However, these strategies made certain social and ethnic groups more vulnerable than others, ultimately contributing to the destruction of the New Mexico colony during the Pueblo Revolt in 1680. We argue that vulnerability buffering mechanisms are unevenly distributed across society. Systems of power must be considered when evaluating the effectiveness of social responses to risk.